Reaffirming the Value of the Autopsy - Sakda Sathirareuangchai (2020)
© 2019 American Society for Clinical Pathology, 2019. All rights reserved. For permissions, please e-mail: journals.permissions@oup.com. To determine characteristic features of myocardial infarction (MI) diagnosed at autopsy and establish the incidence of discrepancy. Methods: Autopsy cases at a tertiary hospital with a pathologic diagnosis of acute MI were evaluated for clinicopathologic features. Modified Goldman's classification was used to classify discrepant cases. Results: Of 529 autopsy cases, 19 (3.6%) demonstrated acute/subacute MI as a pathologic diagnosis. Thrombosis was identified in a minority of cases (3/19, 15.8%). Major clinicopathologic discrepancies were identified in four (21.1%) cases. Conclusions: Although acute MI is an uncommon diagnosis rendered at hospital autopsy, a notable subset of cases demonstrates diagnostic discrepancy between the clinical impression and ultimate pathologic diagnosis. Interestingly, most MI cases in this series are not related to plaque disruption and thus best classified as a type 2 MI, which is associated with imbalance between oxygen demand and supply.